2018
DOI: 10.1002/ags3.12174
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in esophageal cancer treatment in Japan

Abstract: The 11th edition of the Japanese Classification of Esophageal Cancer (EC) was published in 2017. Some correction was made in the depth of tumor invasion to be consistent with the TNM classification by the Union for International Cancer Control (UICC). With regard to surgery, short‐term safety and long‐term effectiveness under thoracotomy/video‐assisted thoracoscopic surgery are expected to be proven by the Japan Clinical Oncology Group (JCOG)1409 study. Results of nutritional management and countermeasures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 82 publications
(70 reference statements)
1
31
0
Order By: Relevance
“…In the present study, the efficacy and safety of the UDON regimen was evaluated as first-line treatment for Japanese patients with advanced or recurrent esophageal cancer (all of whom had squamous cell carcinoma). Consistent with the results of a previous phase I study [1], a high antitumor activity of UDON was found, with an overall response rate (RR) of 72.7%, which is likely equivalent to that for 3-or 4-weekly DCF (docetaxel, cisplatin, and 5-FU) [2] and possibly higher than that for weekly [3] or 2-weekly DCF [4]. Spider plot analysis revealed a rapid response in 11 of the 16 patients showing a partial response (PR), with these individuals achieving tumor shrinkage of ≥30% after one cycle of UDON chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the efficacy and safety of the UDON regimen was evaluated as first-line treatment for Japanese patients with advanced or recurrent esophageal cancer (all of whom had squamous cell carcinoma). Consistent with the results of a previous phase I study [1], a high antitumor activity of UDON was found, with an overall response rate (RR) of 72.7%, which is likely equivalent to that for 3-or 4-weekly DCF (docetaxel, cisplatin, and 5-FU) [2] and possibly higher than that for weekly [3] or 2-weekly DCF [4]. Spider plot analysis revealed a rapid response in 11 of the 16 patients showing a partial response (PR), with these individuals achieving tumor shrinkage of ≥30% after one cycle of UDON chemotherapy.…”
Section: Discussionsupporting
confidence: 86%
“…The median PFS was 6.0 months (range, 0.9 months to not reached), and the median OS was 11.2 months (range, 4.0 months to not reached). The high antitumor efficacy of UDON was also reflected in survival, with a median PFS and OS of 6.0 and 11.2 months, respectively, values that are again similar to those for DCF , which has yielded a median PFS and OS of 5.8–7.0 months and 11.1–13.0 months, respectively.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Further studies are required to elucidate the differences in 53 BP1 expression in non-neoplastic lesions between healthy subjects and patients with SCC. It has been suggested that HG-IN, as well as CIS, should be subjected to endoscopic treatment [5]. Furthermore, according to the most recent Japanese guideline on esophageal carcinoma, HG-IN is histologically defined as a CIS [5].…”
Section: Discussionmentioning
confidence: 99%
“…When the full thickness of the epithelium is involved, it is classified as carcinoma in situ (CIS). HG-IN, CIS, and early SCC limited to the lamina propria are suitable for endoscopic treatment [4,5]. As the prognosis of advanced esophageal SCC is poor, it is of clinical interest to detect lesions suitable for treatment during the early phase.…”
Section: Introductionmentioning
confidence: 99%